Tax burden and tax evasion in Brazil - de Carvalho, Hugo Leonardo Menezes; de Ávila, Lucimar Antônio Cabral (International Journal of Advanced Engineering Research and Science, 2022)
The study analyzed the relationship between the Brazilian tax burden and the country's level of evasion. The basis for the research stems from the fact that Brazil is considered a country whose tax burden is high and this would influence its level of evasion. However, there are international studies that have not identified significance in this relationship and, in the Brazilian case, despite being a widely discussed topic, the literature is incipient in testing this interaction. In view of this gap, the multiple linear regression method was used, based on data from the period from 2005 to 2015. The results showed that, in the Brazilian case, the tax burden presented statistical significance related to tax evasion, confirming the theoretical assumptions used. The present research also suggests that the Theory of Equity can be useful in improving the understanding of tax evasion behavior and the possibility of comparison with international studies.